2020
DOI: 10.1016/j.energy.2020.118398
|View full text |Cite
|
Sign up to set email alerts
|

Energy efficiency in the industrial sector in the EU, Slovenia, and Spain

Abstract: ‘Energy efficiency first’ is one of the key principles of the Energy Union, mainly due to it being the most cost effective way to reduce emissions, improving energy security, enhancing competitiveness and making energy consumption more affordable for all consumers. In light of the revised EU Energy Efficiency Directive, this paper discusses new developments brought by the EU together with the national case studies of Slovenia and Spain. Given that the paper has a specific focus on the industrial sector, it discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(29 citation statements)
references
References 36 publications
0
29
0
Order By: Relevance
“…From this very piece of evidence, it can be inferred that the energy efficiency achieved in the MENA countries is gradually being recognized as a driver of economic transformation, alongside being one of the major tools to achieve energy security in these nations. Moreover, energy efficiency can also be one of major drivers of Industry 4.0, as identified by Malinauskaite et al (2020) and Sinha et al (2020a). These causal associations might be crucial in developing the policies for sustainable development in the MENA countries.…”
Section: Resultsmentioning
confidence: 99%
“…From this very piece of evidence, it can be inferred that the energy efficiency achieved in the MENA countries is gradually being recognized as a driver of economic transformation, alongside being one of the major tools to achieve energy security in these nations. Moreover, energy efficiency can also be one of major drivers of Industry 4.0, as identified by Malinauskaite et al (2020) and Sinha et al (2020a). These causal associations might be crucial in developing the policies for sustainable development in the MENA countries.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers have mainly aimed to introduce technologies or improve efficiency in the full industrial sector or country scale. For example, Malinauskaite et al [16] discussed the energy saving potential of efficiency improvements in the industrial sectors of Slovenia and Spain in relation to the revised Energy Efficiency Directive (EED).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Meta DDF model China's meta-frontier total-factor carbon emission efficiency of high-tech industry was the highest, followed by that of middle-tech industry, with the lowest being low-tech industry. Malinauskaite et al 40 DEA model After the implementation of the new policy, the energy efficiency of Slovenia and Spain has been significantly improved. Wang et al 41 SBM DEA model The static efficiency of carbon emissions in airlines showed an inverted U-shaped trend during the inspection period.…”
Section: Camioto Et Al 28mentioning
confidence: 99%
“…Meta DDF model China's meta-frontier total-factor carbon emission efficiency of high-tech industry was the highest, followed by that of middle-tech industry, with the lowest being low-tech industry. Malinauskaite et al 40…”
Section: Dea Window Modelmentioning
confidence: 99%